2021
DOI: 10.1590/0100-29452021124
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of soil fertility and banana crop nutrition in the state of Santa Catarina

Abstract: Soil fertility and nutritional imbalance are among the main limitations in banana production. The present study aimed to diagnose soil fertility and nutrition of bananas trees cultivated in the state of Santa Catarina, southern Brazil. Leaf and soil samples were collected, and banana yield was quantified in 2018 and 2019 in 53 orchards in the regions of ‘Vale do Itajaí’ and northern coast of Santa Catarina. Although orchards had satisfactory yield (42 t /ha/year), limitations related to soil fertility and bana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…The high variability of P and K levels in commercial orchard soils, as well as banana productivity, indicate the heterogeneity of the banana plantations, cultivated in SC (Table 1). As presented by Guimarães and Deus (2021), the high levels of these nutrients in the soil can be attributed to the absence of adequate nutritional management, which besides favoring the nutritional imbalance of the banana plant, also generate unnecessary costs with fertilizers. Even in orchards with relative production below 70 % (< 54.3 t/ha) the average P and K levels in the soil are higher than the CL considered suitable for fruit trees in Santa Catarina (CQFS-RS/SC, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high variability of P and K levels in commercial orchard soils, as well as banana productivity, indicate the heterogeneity of the banana plantations, cultivated in SC (Table 1). As presented by Guimarães and Deus (2021), the high levels of these nutrients in the soil can be attributed to the absence of adequate nutritional management, which besides favoring the nutritional imbalance of the banana plant, also generate unnecessary costs with fertilizers. Even in orchards with relative production below 70 % (< 54.3 t/ha) the average P and K levels in the soil are higher than the CL considered suitable for fruit trees in Santa Catarina (CQFS-RS/SC, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…When diagnosing soil fertility and the nutritional status of banana plantations in Santa Catarina, Guimarães and Deus (2021) found that 85 and 64 % of the sampled commer-Método da linha de fronteira na atualização dos níveis críticos de fósforo e de potássio no solo em bananais catarinenses Resumo -O uso racional de corretivos e de fertilizantes em pomares de bananeira depende de padrões confiáveis de interpretação da fertilidade do solo. O trabalho objetivou estabelecer níveis críticos (NC) para fósforo (P) e potássio (K) no solo, em bananais de Santa Catarina, usando o método de Linha de Fronteira (LF).…”
Section: Introductionunclassified
“…The mean fruit yield of 'Prata' banana (36,131 kg ha −1 ) in the database (n = 867) used to establish the nutritional standards is approximately twice as high as the national average, which is 14,754 kg ha −1 (FAOSTAT 2021), indicating that the database contemplated a wide variation of yield. This is an indication that the data used to establish nutritional standards are adequate, since they include high-yield orchards (Nachtigall and Dechen 2007), a condition that is only achieved with orchard adequate management practices, among which the indispensable nutritional balance (Deus et al 2018;Guimarães and Deus 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In the last 6 decades (1961 to 2019), the world average yield increased from 10.7 to 22.6 t ha −1 , while the Brazilian average remained stagnant around 15 t ha −1 (Deus et al 2020;FAOSTAT 2021). Studies indicate that, nutritional imbalance is the main cause of low yields in the banana orchards of Brazil and that there is great potential to increase this yield, rebalancing the supply of nutrients (Deus et al 2018;Guimarães and Deus 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, the average yield of this crop is low, 14.6 t ha -1 . This is associated with the cultivated genotypes, nutritional (Guimarães;Deus, 2021) and non-nutritional problems, and biotic, climatic and management factors Neves;Donato, 2021).…”
Section: Introductionmentioning
confidence: 99%